Skeletal involvement in Gaucher disease: An observational multicenter study of prognostic factors in the Argentine Gaucher disease patients. Issue 10 (22nd August 2016) - Drelichman, Guillermo; Fernández Escobar, Nicolás; Basack, Nora; Aversa, Luis; Larroude, María Silvia; Aguilar, Gabriela; Szlago, Marina; Schenone, Andrea; Fynn, Alcyra; Cuello, María Fernanda; Aznar, Marcela; Fernández, Ramiro; et al.
Abstract : Patients with Gaucher type 1 (GD1) throughout Argentina were enrolled in the Argentine bone project to evaluate bone disease and its determinants. We focused on presence and predictors of bone lesions (BL) and their relationship to therapeutic goals (TG) with timing and dose of enzyme replacement therapy (ERT). A total of 124 patients on ERT were enrolled in a multi‐center study. All six TG were achieved by 82% of patients: 70.1% for bone pain and 91.1% for bone crisis. However, despite the fact that bone TGs were achieved, residual bone disease was present in 108 patients on ERT (87%) at time 0. 16% of patients showed new irreversible BL (bone infarcts and avascular osteonecrosis) despite ERT, suggesting that they appeared during ERT or were not detected at the moment of diagnosis. We observed 5 prognostic factors that predicted a higher probability of being free of bone disease: optimal ERT compliance; early diagnosis; timely initiation of therapy; ERT initiation dose ≥45 UI/kg/EOW; and the absence of history of splenectomy. Skeletal involvement was classified into 4 major phenotypic groups according to BL: group 1 (12.9%) without BL; group 2 (28.2%) with reversible BL; group 3 (41.9%) with reversible BL and irreversible chronic BL; and group 4 (16.9%) with acute irreversible BL. Our study identifies prognostic factors for achieving best therapeutic outcomes, introduces new risk stratification for patients and suggests the need for a redefinition of bone TG. Am. J. Hematol. 91:E448–E453, 2016. © 2016 Wiley Periodicals, Inc.